Black Sea–Caspian sprat (tyulka) industrial fishing in the Azov Sea: Presently used fisning gear, methods, and its current trends - Stafikopulo, Aleksei; Vtyurina, N.V.; Gorbatyuk, Ya.I. (2023)
This paper presents the main fishing methods and gears previously used or appraised and currently applied in the course of Black Sea–Caspian sprat (tyulka) fishing in the Azov Sea: their performance, merits and demerits. Black Sea–Caspian sprat (tyulka) fishing comprises the coastal fishing with pound nets and the fishing off the board of fishing vessels with purse seines ans midwater trawls. Recently, sprat catches with pound nets have been on the decline; meanwhile, use of fishing vessels, albeit more resource-consuming and dependent on the multitude of factors, can prospectively be more productive than the coastal fishing, even though currently it shows lower catches. A brief characterization of the Black Sea–Caspian sprat (tyulka) industrial fishing in the recent years is given, its trends and challenges are discussed. Daily vessel reports have been processed for 2015–2021, and the comparative data on the operation of the vessels of various types are presented; the trends in the changing industrial fishing parameters during the investigated period show a considerable decrease in all the parameters. Another crucial issue is the necessity to reduce the by-catch of non-target fish species (sturgeons, Black Sea turbot) in long-continued depressed state with midwater trawls. The presented data will allow for the current status assessment of the Black Sea–Caspian sprat (tyulka) industrial fishing and envisioning the efficient, yet selective and environmentally sound fishing methods to be developed and revised. В статье рассмотрены основные способы и орудия лова, которые применялись или апробировались ранее, а также используются в настоящее время при промысле тюльки в Азовском море, их производительность, достоинства и недостатки. Промысел тюльки состоит из прибрежного промысла ставными неводами и судового промысла кошельковыми неводами и разноглубинными тралами. Вылов тюльки ставными неводами в последнее время ежегодно снижается, в то время как судовой промысел — более сложный и зависящий от многих факторов — ...